Hepatic Portal Venous Gas: An Ill Omen or a Misleading Sign - Mehta, Shruti (Surg J (N Y), 2020)
Hepatic portal venous gas (HPVG), a rare radiological finding, is historically considered an ominous sign with 100% mortality rates. The dictum that HPVG warrants surgical intervention is challenged in the recent literature. This is because of the identification of various causes of HVPG other than bowel gangrene. Most of these newly identified causes can be managed conservatively. However, bowel gangrene, if missed, is fatal. Hence, sound clinical judgment and accurate diagnosis based on specific clinical parameters and imaging findings are important. We present a case of a young male with tumor lysis syndrome and neutropenic sepsis. He underwent treatment for a relapse of T-cell acute lymphocytic leukemia and presented with abdominal pain and distension. Computed tomography (CT) scan showed HPVG, and the differential diagnosis was neutropenic colitis or pseudomembranous colitis, with steroid use as the probable cause. The patient was managed conservatively. The case emphasizes that the evaluation for a specific cause of HPVG is important to reduce unnecessary surgery. A succinct literature review provides the reasons for the changing mortality rates.